The Parameters of Emergency Disaster Hospital with Inflatable Pneumatic Structure (International Conference of Graduate School on Sustainability (ICGSS), 2020)
This Research Design begins from the problems at handling sick inhabitants and emergency medical facility on disaster areas. Speed and Efficiency at handling disasters, effective preventive measures, rehabillitation and recovery, on time delivery of disaster relief will minimize negative results after the disasters happened. Disaster relieves are intended to shelter a lot of disaster victims in a livable and comfortable building, one of the disaster countermeasures facility is Disaster Emergency Hospital, which is consist of basic diagnostic equipments and treantments that is : Triage, ICU, Operation Room, Therapy/Treatment, Consultation room, Radiology, Laboratory/Diagnostic, Pharmacy. Until today, Integrated Disaster Emergency Hospital Facility is not yet available in Indonesia, some of disasters that happened in Indonesia only facilitated with health post with tents or emergency building built with conventional structure and technology which is steel frame tent with a high cost and long time to build. Therefore, Disaster Emergency Hospital need a structure that can be built in a short period of time, using pneumatic air inflated structure. The Disaster Emergency hospital design concept are focused on speed and efficiency in handling the patients so that will help the healing process. The research method for the design of the Disaster Emergency Hospital is  using evidence based design that is a design based on scientific evidence in form of earlier research results and own research. There are 5 parameters in the design of the Disaster Emergency Hospital, that is : mobility, portable, build speed, safety and convenience for the patients and the medical personnels.